Radical Resection of Differentiated Thyroid Cancer in Elderly Patients: Evaluation of the Efficacy of the Immunocolloidal Gold Strip Method Combined with Nanocarbon Negative Imaging Tracing Technology for Parathyroid Gland Imaging - YanBin Liu; LiJuan Zuo; YunChao Xin; YaChao Liu; ZeDong Tian; XiaoLing Shang (Journal of Investigative Surgery)
Objective Extant imaging methods used for the proper identification of the parathyroid glands to prevent post-operative hypothyroidism associated with the resection of differentiated thyroid cancer (DTC) are limited by factors such as low specificity, high cost, and technical complexity. This study, therefore, sought to investigate the efficacy of the immunocolloidal gold strip method combined with nanocarbon negative imaging tracing technology for parathyroid gland imaging during radical resection of DTC in elderly patients.Methods A total of 100 elderly patients with DTC were enrolled and randomly divided into two groups: the control group and the observation group. The control group underwent conventional radical thyroidectomy with bilateral cervical lymph node dissection, while the observation group received the immunocolloidal gold strip method combined with nanocarbon negative imaging tracing technology for parathyroid gland imaging during the surgery. The baseline characteristics, intraoperative findings, postoperative parathyroid hormone (PTH), and serum calcium levels, as well as postoperative complications, were compared between the two groups.Results There were no significant differences in age, gender, body mass index, comorbidities, or smoking history between the two groups. The observation group had a significantly higher number of parathyroid glands identified during surgery compared with the control group. The postoperative PTH and serum calcium levels at postoperative days 1 and 3 and at 6 months were significantly higher in the observation group than those in the control group. The incidence of postoperative hypoparathyroidism was significantly lower in the observation group.Conclusion The immunocolloidal gold strip method combined with nanocarbon negative imaging tracing technology is effective in identifying and preserving parathyroid glands during radical resection of DTC in elderly patients.